Soil Nutrients, Bacteria Populations, and Veterinary Pharmaceuticals across a Backgrounding Beef Feedlot. Issue 2 (1st March 2013) - Netthisinghe, A. M. P.; Cook, K. L.; Rice, C.; Gilfillen, R. A.; Sistani, K. R.
Abstract : Beef cattle backgrounding operations that grow out weaned calves for feedlot finishing contain several environmentally significant constituents. A better understanding of these constituents and their environmental distribution will aid in the development of effective management guidelines for sustainable beef production. This research investigated soil nutrients, bacterial, and veterinary pharmaceutical concentrations across a small backgrounding beef feedlot on a karst landscape. Results indicated that all contaminants were highly concentrated in the feeder area (FD) and were lower in the other feedlot areas. The FD soils had a pH of 8.2, 59 mg kg −1 soil organic matter (SOM), 2002 mg kg −1 soil test phosphorus (STP), 99.7 mg kg −1 NH4 –N, and 18.3 mg kg −1 NO3 –N. The other locations were acidic (5.9–6.9 pH) and contained 39 mg kg −1 SOM, 273 mg kg −1 STP, 21.5 mg kg −1 NH4 –N, and 2.0 NO3 –N mg kg −1 . Bacteria populations in the FD averaged 2.7 × 10 10 total cells, 3.9 × 10 8 Bacteriodes spp., 2.9 × 10 8 Enterococcus spp ., and 4.5 × 10 5 Escherichia coli cells per gram of soil. Bacteriodes spp. and Enterococcus spp. concentrations were 1 to 4 orders of magnitude lower at the other locations. Escherichia coli showed lower dynamic range and was generally uniformly distributed across the landscape. Antibiotic and parasiticide concentrations in the FD were 86.9 ng g −1 monensin, 25.0 ng g −1 lasalocid, and 10.3 ng g −1 doramectin. Their concentrations were 6‐ to 27‐fold lower in the other feedlot locations. Contaminant management plans for this small feedlot will therefore focus on the feeder and nearby grazing areas where soil nutrients, bacteria populations, and veterinary pharmaceuticals were most concentrated.